HIGH INTENSITY INTERVAL TRAINING DOES NOT CHANGE THE AREA IN THE ADIPOCYTES OF THE EPICARDIUM OF FAT RATS (Arquivos do Mudi, 2023)
The obesity due to high caloric ingestion is related to the accumulation of body fat andpredisposes cardiovascular diseases. Recent studies about the High Intensity Interval Training(HIIT) evidence benefits of its practice in patients that maybe carrying this disease, mainlybecause of the reduction of comorbidities associated with obesity. This present study has theobjective of evaluating the HIIT effects on the adipocytes’ changes of the epicardium adiposetissue in fat animals induced by the consumption of high-fat diet. It was used male rats ofWistar lineage fed daily with HFD and trained by HIIT three times a week for 8 consecutiveweeks. The animals were weighted during the training sections and, after its euthanasia, wererealized histological analyses of the epicardium adipose tissue. The results showed that HFDincreased the body weight of the animals and the side view of the adipocytes. However, theHIIT did not change the area of the adipocytes of the epicardial adipose tissue, even thoughthe diet had been a hypertrophy factor of this tissue. Then, we can conclude that HIITcontributes to avoid the body weight gain but was not capable of reducing the area of theadipocytes of the epicardium adipose tissue.